2022
DOI: 10.1126/sciadv.abl5417
|View full text |Cite
|
Sign up to set email alerts
|

Complaints about excessive use of police force in women’s neighborhoods and subsequent perinatal and cardiovascular health

Abstract: There are substantial, unexplained racial disparities in women’s health. Some of the most pronounced involve elevated rates of preterm delivery (PTD) and cardiovascular disease (CVD) among Black women. We hypothesized that stress associated with excessive use of force by police may contribute to these disparities. In two prospective cohorts derived from electronic health records (pregnancy cohort, N = 67,976; CVD cohort, N = 6773), we linked formal complaints of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…30,31 Race-and ethnicity-based differences in related birth outcomes (preterm birth and low birth weight) have also been associated with individual-level reports of racial and ethnic discrimination as well as neighborhood-level factors, such as census-block reports of excessive use of force by law enforcement officers. 32,33 Our analyses also demonstrate greater RRs for the incidence of new-onset HDP among older pregnant individuals at delivery who did not identify as White. This dynamic was associated with widening racial and ethnic gaps for new-onset HDP among older age groups.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…30,31 Race-and ethnicity-based differences in related birth outcomes (preterm birth and low birth weight) have also been associated with individual-level reports of racial and ethnic discrimination as well as neighborhood-level factors, such as census-block reports of excessive use of force by law enforcement officers. 32,33 Our analyses also demonstrate greater RRs for the incidence of new-onset HDP among older pregnant individuals at delivery who did not identify as White. This dynamic was associated with widening racial and ethnic gaps for new-onset HDP among older age groups.…”
Section: Discussionmentioning
confidence: 55%
“… 30 , 31 Race- and ethnicity-based differences in related birth outcomes (preterm birth and low birth weight) have also been associated with individual-level reports of racial and ethnic discrimination as well as neighborhood-level factors, such as census-block reports of excessive use of force by law enforcement officers. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings have broad public health importance given potential implications of fatal police violence for the health of people of the decedent’s community and same racial and ethnic group, which may be even more significant in smaller ethnic groups or tight-knit ethnic communities and/or if these deaths involve immigration enforcement agents [ 19 ]. Recent studies, for example, have indicated that fatal police violence likely has spillover effects, impacting the mental, perinatal, and cardiovascular health of community members with the same racial/ethnic background as decedents [ 20 23 ]. Previous studies of racial/ethnic inequities in police violence have largely ignored national/ethnic heterogeneity within larger racial/ethnic groups [ 2 , 3 , 24 , 25 ], as needed data rarely exists.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Black women living in communities with excessive police force are more likely to experience cardiovascular disease than White women. 17 Cardiovascular diseases are associated with racism, with post-traumatic stress disorder markedly explaining this relationship. 18 …”
Section: Structural Racism and Cardiovascular Health Outcomes For Acb...mentioning
confidence: 99%